2019
DOI: 10.5114/hm.2019.79732
|View full text |Cite
|
Sign up to set email alerts
|

Does a virtual functional training induce cardiovascular responses in normotensive adults after a single session and over weeks?

Abstract: Purpose. Active video games (AVG) provide an attractive alternative to sedentary behaviours and may bring some health benefits. However, single-session and chronic cardiovascular effects of AVG remain unclear. the aim of this study was to verify the impact of single-session and 4-week virtual functional training on cardiovascular responses in normotensive adults. Methods. In a pre-experimental study, 8 university students performed a 30-minute AVG session (Nike Kinect training® game) at the intensity of 64% (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
5
1
5
Order By: Relevance
“…The novelty of this study was that it verfied the acute and late cardiovascular responses and the enjoyment levels of AVG and traditional exercise sessions in T1DM patients. Our data differed from a) previous studies performing AVG and running in non-diabetics, which only considered the immediate acute physiological changes 10,[12][13][14]26 ; b) studies performing only with AVG without traditional exercise comparison in non-diabetics [10][11][12]14,25,26,34 ; c) the study with AVG and traditional exercise modalities in the same training program which does not allow verifying what exercise type was handled metabolic improvements in T1DM 6 ; and d) studies verifying non-diabetics cardiovascular responses after AVG without considering enjoyment levels [10][11][12][13]34 .…”
Section: Clinical Relevance the Novelty And Study Limitationscontrasting
confidence: 91%
See 4 more Smart Citations
“…The novelty of this study was that it verfied the acute and late cardiovascular responses and the enjoyment levels of AVG and traditional exercise sessions in T1DM patients. Our data differed from a) previous studies performing AVG and running in non-diabetics, which only considered the immediate acute physiological changes 10,[12][13][14]26 ; b) studies performing only with AVG without traditional exercise comparison in non-diabetics [10][11][12]14,25,26,34 ; c) the study with AVG and traditional exercise modalities in the same training program which does not allow verifying what exercise type was handled metabolic improvements in T1DM 6 ; and d) studies verifying non-diabetics cardiovascular responses after AVG without considering enjoyment levels [10][11][12][13]34 .…”
Section: Clinical Relevance the Novelty And Study Limitationscontrasting
confidence: 91%
“…These results could prevent atherosclerotic denegation, inflammatory responses, and future coronary risks 2,3 . Previous studies have also verified similar MDD results after AVG and traditional exercise sessions, and have shown that minimum MDD changes could promote cardiovascular and metabolic health 11,26,31 . Therefore, health professionals who work with T1DM patients can use our results for including AVGs as complementary management tools that provide cardiovascular benefits with great enjoyment levels.…”
Section: Clinical Relevance the Novelty And Study Limitationssupporting
confidence: 55%
See 3 more Smart Citations